Parental characteristics (education level) risk of stunting in toddlers - Yunani Yunani; Yuniastini Yuniastini; Purwati Purwati; Al Murhan; Giri Udani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Stunting is a condition where children experience stunted growth due to chronic malnutrition, especially during the first 1.000 days of life. This condition can have long-term impacts on a child's physical, cognitive, and social development. According to data from the World Health Organization (WHO), globally, about 22% of children under five years old experience stunting, with higher prevalence found in developing countries, including Indonesia. In Indonesia, the prevalence of stunting reached 24.4% in 2021, making it one of the significant public health challenges. Data from the Ministry of Health of the Republic of Indonesia shows that various factors contribute to stunting, including environment, economy, and parental characteristics, particularly education level. Research indicates that parents with higher education levels tend to understand the importance of nutrition and child health better, thus reducing the risk of stunting. In Lampung Province, the prevalence of stunting has also become a concern, with a figure reaching 28.3% in 2022. Geographic, social, and economic factors in Lampung can affect parents' knowledge and behavior in maintaining children's health. Purpose: to determine the distribution of risk factors for stunting in toddlers in Noto Harjo village. The specific objective is to determine the prevalence of stunting incidents in toddlers in Noto Harjo village based on Z-Score values, to detect parental characteristics including education level and child development monitoring behavior. Method: This study is designed as quantitative research using a survey design. The total population and sample of all toddlers in the Noto Harjo sub-district is 224 people, with 112 samples taken through observation techniques (height measurement), interviews with the parents of toddlers, and documentation studies. Data analysis uses a descriptive approach. Results: The research results show that the stunting rate is 21.4 percent, which is almost the same as the prevalence of stunting in Indonesia (21.6 percent). However, the government aims to achieve a stunting rate of 14% by 2024. To achieve this, various collaborative efforts are needed. Conclusion: The research results show that the prevalence of stunting in toddlers in Notoharjo Village reaches 21.4%. This is nearly equivalent to the national prevalence of stunting in Indonesia, which stands at 21.6%. However, this prevalence is still far above the government target of 14% by 2024. This indicates that stunting requires more intensive handling, which includes nutritional interventions, raising community awareness, and better policy support. It is hoped that all parties will work together to achieve the stunting reduction target, so that children in Indonesia can grow up healthy and optimally.